ECONOMIC ANALYSIS OF MARKETING PERFORMANCES AT LEDUG COFFEE INDONESIA - Fahmila, Nada Alifiyah; Winarno, Sri Tjondro; Atasa, Dita (Yayasan Education and Social Center, 2023)
This study aims to 1) Know the channel pattern and marketing function of Ledug Coffee Indonesia, 2) Analyze the marketing margin of Ledug Coffee Indonesia, and 3) Analyze the level of marketing efficiency of Ledug Coffee Indonesia. Using the snowball sampling technique, 4 agents and 9 retailers were found to find out the marketing channel chain. The data analysis used was marketing margin, K/B ratio, and producer share. The results of this study indicate that there are three marketing channels: channel I (producer-retailer-end consumer), channel II (producer-agent-retailer-end consumer), and channel III (producer-end consumer). The smallest marketing margin is owned by marketing channel III, on the robusta IDR 2,000 / kg type and Arabica IDR 85,000 / kg. Marketing channels that have the most efficient level of efficiency is channel III because efficiency indicators show that all hands are efficient.